Essential commodities prices, availability, and market actors’ perceptions: August 2025 - Siddig, Khalid; Rakhy, Tarig; Abushama, Hala; Mohamed, Shima; Nigus, Halefom Yigzaw (International Food Policy Research Institute, 2025)
This report presents an overview of trends in prices, availability, and quality of key commodities, while also capturing traders’ perceptions of supply, demand, and market conditions in Sudan between February and August 2025.